1998
DOI: 10.1080/15438629809512527
|View full text |Cite
|
Sign up to set email alerts
|

Serum creatine kinase, CK‐MB, and perceived soreness following eccentric exercise in oral contraceptive users

Abstract: Estrogen ingestion has been suggested as a protective mechanism of muscle membrane integrity against an exercise-induced muscle inflammatory response. Serum creatine kinase (CK) concentration and the heart muscle isoenzyme CK-MB have been used as diagnostic markers of muscle disruption following exercise. The purpose of this study was to determine the difference in serum CK, CK-MB, and perceived soreness following exercise-induced muscle disruption in females taking an oral contraceptive (OC) and those not. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…We measured several biomarkers indicative of muscle damage (CK, myoglobin, LDH, and hsCRP) to determine if the use of OCs was associated with greater muscle damage in response to resistance exercise. Higher CK activity in OC users compared with nonusers after eccentric exercise has been found in some (7,9,12) but not all studies (10,11). We observed significant increases in CK activity after resistance exercise but no significant difference between groups.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…We measured several biomarkers indicative of muscle damage (CK, myoglobin, LDH, and hsCRP) to determine if the use of OCs was associated with greater muscle damage in response to resistance exercise. Higher CK activity in OC users compared with nonusers after eccentric exercise has been found in some (7,9,12) but not all studies (10,11). We observed significant increases in CK activity after resistance exercise but no significant difference between groups.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, the effect that different forms of progestins in OCs may have on skeletal muscle properties has only been scarcely studied (6). Muscle recovery and exercise-induced muscle damage have been compared between untrained OC users and nonusers in a handful of studies (7)(8)(9)(10)(11)(12). Muscle damage was induced by eccentric muscle contractions in the lower (7,(9)(10)(11)(12) or upper extremities (8), and recovery measures were collected before and up to 162 h after exercise.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, oestrogen is typically much lower in older post-menopausal women than young women, and this reduction in hormone levels could explain the impaired exercise recovery rates in older compared to younger women. Although this has not yet been investigated, a previous systematic review [72] found five studies that reported markers of EIMD in young women who were or were not taking oral contraceptives [73][74][75][76][77]. In the one study in which endogenous oestrogen was higher prior to exercise in the oral contraceptive group, a lower CK response was reported post-exercise compared to the menstrual cycle group [77], suggesting a potential protective effect of oestrogen against EIMD.…”
Section: The Effect Of Age On Exercise-induced Muscle Damage In Womenmentioning
confidence: 99%
“…Although this has not yet been investigated, a previous systematic review [72] found five studies that reported markers of EIMD in young women who were or were not taking oral contraceptives [73][74][75][76][77]. In the one study in which endogenous oestrogen was higher prior to exercise in the oral contraceptive group, a lower CK response was reported post-exercise compared to the menstrual cycle group [77], suggesting a potential protective effect of oestrogen against EIMD. However, like the present review, no conclusions could be drawn due to a relatively small number of varied studies.…”
Section: The Effect Of Age On Exercise-induced Muscle Damage In Womenmentioning
confidence: 99%